High Concomitant Misuse of Fentanyl in Subjects on Opioid Maintenance Treatment. (16th April 2017) - Krause, Daniela; Plörer, Diana; Koller, Gabriele; Martin, Gabi; Winter, Catja; Adam, Roland; Canolli, Minavere; Al-Iassin, Jori; Musselmann, Rainer; Walcher, Stephan; Schäfer, Frank; Pogarell, Oliver
ABSTRACT: Background : Concomitant opioid misuse is an increasing problem in opioid maintenance treatment as it interferes with treatment success. Objective: Therefore, the rates of concomitant fentanyl misuse in opioid maintained patients were investigated. Methods : We conducted a cross-sectional study which consisted in collecting data via urine samples and questionnaires in Germany. Urine samples of patients on opioid maintenance treatment were gathered and fentanyl concentrations were measured from 2008 to 2012. An anonymous questionnaire provided data on the consumption of fentanyl as concomitant drug. Data were analyzed with descriptive statistics and group differences were calculated using the Chi-Square test. Results : Among the total sample (urine probes of 960 patients), 6.8% opioid maintained patients had positive urine samples for fentanyl and 37.9% reported concomitant fentanyl misuse (401 of these patients filled out the questionnaire). A significant age-related association of concomitant fentanyl misuse was identified in the urine analyses (χ 2 = 7.489; p = .024) and also in the questionnaire data (χ 2 = 11.899, p = .003), indicating that young age increased the probability of fentanyl consumption. Patients receiving methadone had the highest rates of concomitant fentanyl misuse with 18.4% according to urine analysis. In addition, the results show that patients who are on diamorphine are significantly less likely to misuse fentanyl. Conclusions : Fentanyl is a frequently used concomitant drug. Especially young patients and patients taking methadone are at high risk. Because of the life-threatening consequences of fentanyl overdose, patients taking fentanyl should be intensively medically surveilled.